Phosphorus Shapes Soil Microbial Community Composition and Network Properties During Grassland Expansion Into Shrubs in Tibetan Dry Valleys - Zhou, Hanchang; Ma, Anzhou; Zhou, Xiaorong; Chen, Xianke; Zhang, Jiejie; Zhang, Qinwei; Qi, Xiangning; Liu, Guohua; Zhuang, Guoqiang (Frontiers in Plant Science, 2022)
Alpine ecosystem stability and biodiversity of the Tibetan plateau are facing threat from dry valley vegetation uplift expansion, a process which is highly connected to variations in the soil microbial community and soil nutrients. However, the variation of microbial community properties and their relationship to soil nutrients have scarcely been explored in Tibetan dry valleys, which is a gap that hampers understanding the dry valley ecosystem’s response to vegetation change. In this study, we sampled grasslands (G), a grass-shrub transition area (T), and shrublands (S) along an uplift expansion gradient and investigated the link between microbial community properties and soil nutrients. The results showed that shrub degradation by grass expansion in Tibetan dry valley was accompanied by increasing relative phosphorus (P) limitation, which was the main driver for bacterial and fungal composition variation as it offered highest total effect on PC1 (0.38 and 0.63, respectively). Total phosphorus (TP) was in the center module of bacterial and fungal network under shrub soil and even acted as key nodes in fungal networks. During the replacement by grass, TP was gradually marginalized from both bacterial and fungal center network module and finally disappeared in networks, with ammonia and nitrate gradually appearing in the bacterial network. However, TC and total nitrogen (TN) were always present in the center modules of both fungal and bacterial network. These support that a TP variation-induced compositional and network functional shift in the microbial community was a potential reason for vegetation uplift expansion in Tibetan dry valley. This study highlighted the effect of TP on microbial community properties during dry valley vegetation uplift expansion and offered basic information on Tibetan alpine dry valley ecosystem’s response to climate change.